“Missionary for Culture”: Walter Abell, Maritime Art and Cultural Democracy, 1928-1944 - Niergarth, Kirk (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2006)
Abstract During his years in Nova Scotia, Walter Abell became an influential critic, scholar and arts activist. Even though Abell’s efforts to nationalize Maritime art institutions and initiatives can be seen to have contributed to central-Canadian domination of cultural institutions, it should be recognized that Abell understood his actions very differently and that he thought his Maritime-based experiments in what he called “cultural democracy” could be expanded across the country. Abell’s perception, however, that his goal of a participatory, cooperative, community-based culture was the common aim of Canada’s elites and institutions was perhaps his greatest misjudgment.